2012
DOI: 10.1002/mus.23342
|View full text |Cite
|
Sign up to set email alerts
|

Zoster‐associated mononeuropathies (ZAMs): A retrospective series

Abstract: While ZAM is an uncommon occurrence following cutaneous HZ, it is associated with significant weakness, high rates of post-herpetic neuralgia, and prolonged morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Normally, MRI scanning is not performed in patients with uncomplicated zoster. A PubMed search of patients with zoster paresis (lower motor neuron weakness corresponding to the dermatome where rash was present) revealed that MRI scans are normal [1-4] or that spinal cord lesions are present 1-2 levels adjacent to the area of segmental weakness [5-7]. Thus, to our knowledge, this is the first report of widespread subclinical imaging abnormalities far beyond the site of zoster and focal zoster paresis.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, MRI scanning is not performed in patients with uncomplicated zoster. A PubMed search of patients with zoster paresis (lower motor neuron weakness corresponding to the dermatome where rash was present) revealed that MRI scans are normal [1-4] or that spinal cord lesions are present 1-2 levels adjacent to the area of segmental weakness [5-7]. Thus, to our knowledge, this is the first report of widespread subclinical imaging abnormalities far beyond the site of zoster and focal zoster paresis.…”
Section: Discussionmentioning
confidence: 99%
“…Electroneuromyography (ENMG) can help with the differential diagnosis of entrapment syndrome or radiculopathies, and may reveal variable electrophysiological findings in zoster-associated mono neuropathies (12,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of upper-limb herpes zoster patients presenting with concomitant paresis or paralysis (12,14). Notwithstanding motor involvement in herpes zoster can be diagnosed by ENMG, subclinical motor involvement is most likely underrecognized and underdiagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation can be helpful to diagnose a patient with postherpetic neuralgia presenting after a variable asymptomatic period 21. MRI studies can also demonstrate abnormalities on affected nerves 20. Zoster-associated mononeuropathies may cause variable electrophysiological findings on ENMG investigation 20–22.…”
Section: Discussionmentioning
confidence: 99%